Lithospheric structure based on integrated analysis of geological-geophysical data along the DOBREfraction’99/DOBRE-2 profile (the East European Platform —the East Black Sea Basin) - I. Pashkevich; O. Rusakov; R. Kutas; D. Gryn; V. Starostenko; T. Janik (Геофизический журнал, 2018)
The continuous DOBREfraction’99/DOBRE-2 WARR and CDP profile of 775 km length with about 100 km overlap was acquired by an international team from Ukraine, Poland, Denmark, USA, Netherlands, Germany, Great Britain and Norway in 1996 and 2007 respectively. It crosses southeastern East European Craton (the southern slope of the Voronezh Massif, Donbas, the Priazov Megablock), the North Azov Trough, the Middle Azov High, the Indolo-Kuban Depression, the Crimea-Caucasus inversion zone, the Sorokin Trough, the Shatsky and Andrusov Ridges in the Eastern Black Sea Basin. In terms of the number of tectonic structures of different ages and origin, the profile has no analogues in world practice. Along the profile there has first been carried out an interdisciplinary geological and geophysical study of the entire lithospheric cross-section with the use of seismic data, magnetic, gravity and thermal fields, information on seismic tomography and spontaneous electric emission of the Earth. Fundamentally new information has been obtained for the structure of the lithosphere and a number of controversial problems have been convincingly solved. Tectonically, the lithosphere is a complex collage of structures arised in different geodynamic conditions from the Archean to the Neogene as a result of successive stages of its formation. The regional regularities in the structure of the lithosphere are the decrease in the thickness of the crust from north to south, from ancient structures to young ones with simultaneous elevation of the top of asthenosphere from 210 km under the Voronezh Massif to 90 km under the East Black Sea Basin. The standard continental crystalline crust has been mapped on the southern slope of the Voronezh Massif and in the Priazov Megablock. It has been reworked by the Paleozoic rifting in Donbas. The analysis of the heterogeneity of the crystalline crust and mantle has first been used to assess the position of the actual boundary of the East European Platform and the transition zone to the Scythian Plate, which corresponds to the deepest position of the asthenosphere top and the division between domains of different seismic velocities in the lithospheric mantle. The changes in the crystalline crust type under the Main Azov Thrust fixes the buried boundary of the East European Platform. The relationship has been established between large sedimentary structures and the areas of change in the composition of the crystalline crust along suture zones. The main faults of the sedimentary cover as the sutures of different ages have been traced in the cross-section of the crystalline crust and in the upper mantle. The subcrustal decomposition of the mantle and the crust—mantle mixture at the base of the crust of the maximum thickness between the South Crimean and Mesozoic sutures and in Donbas have resulted from the lithosphere reworking during its development. Different types of crystalline crust and gentle inclined intracrustal disturbances sometimes causing doubling different layers of the crystalline crust provide evidence of repeated subduction of the oceanic crust of the Paleo-, Mezo- and Neotethys. The low-velocity mantle layer between the South Crimean and Mesozoic sutures indicates a present-day manifestation of the total effect of post-Paleozoic subductions. A set of possible rocks has been determined for the crystalline crust within the southern slope of the Voronezh Massif, Donbas and the Azov Mega block. In the Crimea-Caucasus inversion zone at a depth of 30 km a complex of rocks has been documented to be inherent in the standard continental crust which is an alternative to the speculation about the local elevation of the upper mantle due to the serpentinization of mafic rocks.